Neonatal Pneumonia in NICU of a Tertiary Care Center - Mannan, MA; Nahar, Nazmun; Ahmed, Firoz; Jahan, Ismat; Mosleh, Taskina; Khan, Kamrul Ahsan; Dey, Sanjoy Kumer; Shahidullah, Mohammod (Bangladesh Journal of Child Health, 2018)
Background: Pneumonia is one of the causes of neonatal infection and responsible for significant morbidity and mortality, especially in developing countries. The study was aimed to reveal frequency and outcome of pneumonia among hospitalized sick newborn of neonatal intensive care unit. Methodology: This observational study was carried out in the NICU of Bangabandhu Sheikh Mujib Medical University (BSMMU) on 94 neonates with the diagnosis of pneumonia admitted from July 2012 to June 2014. All studied neonates were subjected to history taking, clinical examination, routine investigations, chest radiography and blood culture and sensitivity. Results: Incidence of neonatal pneumonia was 43% among admitted neonates with respiratory distress. Mean birth weight and gestational age were 2392±854 and 33±3.9 weeks respectively. Of enrolled infants with pneumonia, 38 (40.4%) were early onset, 24 (25%) were hospital acquired pneumonia and community acquired pneumonia was documented in 14 (14.8 %) and the rest 18 (19%) were ventilator associated pneumonia. Blood culture was positive in 18 (19%) of cases with neonatal pneumonia; most common pathogen isolated was acinetobacter. Mean duration of hospital stay was 19±8 days. Most of the neonatal pneumonia were cured 72 (76%) with therapy, whereas 17 (18%) died during their hospital course. Conclusion: Overall incidence among admitted sick neonates was 8.4% which constituted 34% of distressed neonate. Bangladesh J Child Health 2018; VOL 42 (3) :112-117